Penerapan Teknologi Solid Fuel Briket Limbah Baglog Jamur Tiram dalam Program Bina Desa menjadi Petani Jamur - Aisiyah, Muktamar Cholifah (Lembaga Yasin AlSys, 2022)
Implementing the village program for village youth to become oyster mushroom farmers in Kadungrembug Village, it is best if they need support in managing the waste produced. The waste produced by mushroom farmers is baglog waste, which is generally used as fertilizer. The purpose of this activity is in the form of transfer of solid fuel technology. The applied solid fuel technology transfer is briquettes. This is supported by the process of making baglog which requires a lot of fuel, such as woods, to be used for media sterilization. The method used is socialization and mentoring, namely the introduction of briquettes and briquette-making technology. The impact on the implementation of solid fuel technology transfer is the efficiency of spending for mushroom farmers to buy firewood and solving the problem of waste with a higher selling value by implementing the making of briquettes. From the results of the questionnaires distributed to the village youth both before and after the activity, it was shown that there was a very significant increase in the understanding of village youth in solving the problem of oyster mushroom cultivation waste and supporting the economy in oyster mushroom cultivation.